Collaborating with radiographers to address their work-related musculoskeletal discomfort. (May 2020) - Sommerich, Carolyn M.; Lavender, Steven A.; Evans, Kevin D.; Sanders, Elizabeth B.-N.; Joines, Sharon; Lamar, Sabrina; Radin Umar, Radin Zaid; Yen, Wei-Ting; Park, SangHyun
Abstract: The prevalence of musculoskeletal (MSK) symptoms in radiographers is high, similar to other healthcare occupations that involve high levels of physical exertion (e.g. patient handling; grasping and moving equipment). Reports of interventions to reduce MSK discomfort in radiographers are limited. A participatory approach was used to investigate daily challenges, needs, and opportunities for developing interventions to address exposures to many of the risk factors that contribute to MSK symptoms in radiographers. In this paper, we present the expressed needs of experienced radiographers (including assistance with patient handling, security, supportive design of equipment and work spaces), along with their evaluations of several intervention concepts intended to address some of those needs. We also report results from tests of three prototype interventions stemming from this participatory process that demonstrate the potential for new engineering control concepts to reduce the physical effort associated with some of the most common tasks radiographers perform. Highlights: Patient handling is an important risk factor for MSK injuries in radiographers. Participatory design illuminates work context and intervention needs. Patient handling solutions must be tailored to radiographer's work context. Engaging radiographers in participatory design produces novel intervention concepts. Patient handling solutions can benefit radiographers and patients.